Optimal Placement and Sizing of Distributed Generators Based on Swarm Moth Flame Optimization - Tan, Zhukui; Zeng, Ming; Sun, Liming (Frontiers in Energy Research, 2021)
In order to deal with the problem of environmental pollution and energy consumption, developing clean and renewable energy to maintain the sustainable development of society has become an urgent matter for human beings. Therefore, distributed generation (DG) is widely concerned by engineers. However, the output of DG is generally random and intermittent. When it is connected to different locations, different capacities and different types of power grids, the safe and stable operation of the power system will be affected to different degrees. When selecting the optimal DG access scheme, power grid planners must consider the influence of capacity, type and location to ensure a safer, more stable, more reliable and more efficient power grid operation. Therefore, this paper proposes an objective function considering integrated power losses, voltage profile and pollution emission, and swarm moth flame optimization algorithm (SMFO) is used to solve. Finally, based on IEEE-33 bus, the effectiveness of the proposed algorithm is verified.